1998
DOI: 10.1046/j.1420-9101.1998.11020159.x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inheritance in evolution

Abstract: We discuss the role of cell memory in heredity and evolution. We describe the properties of the epigenetic inheritance systems (EISs) that underlie cell memory and enable environmentally and developmentally induced cell phenotypes to be transmitted in cell lineages, and argue that transgenerational epigenetic inheritance is an important and neglected part of heredity. By looking at the part EISs have played in the evolution of multicellularity, ontogeny, chromosome organization, and the origin of some post-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
0
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(161 citation statements)
references
References 82 publications
5
147
0
5
Order By: Relevance
“…410 He also endorsed Alexander Bain's "fundamental law of pleasure and pain," which states that pleasure is connected with an increase and pain a decrease in vital power (the tit-fortat self-regulatory code), a law founded upon "the principle of self-conservation, the self-regulating, selfacting impulse of the animal system" 411 (emphasis mine). Had Darwin been privy to modern understandings of the chemical networks, computational, and regulatory dynamics involved in genetics, epigenetic inheritance, 42,186 social genomics, 193 and neuroplasticity, 412 it seems likely he would have noted the importance of here-and-now environmental interactions and behavioral responses, and perhaps more pointedly given emotion its functional due. Still, despite his laudable parsimony, Darwin concluded that "the 'language of emotion' is certainly of importance for the welfare of mankind."…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…410 He also endorsed Alexander Bain's "fundamental law of pleasure and pain," which states that pleasure is connected with an increase and pain a decrease in vital power (the tit-fortat self-regulatory code), a law founded upon "the principle of self-conservation, the self-regulating, selfacting impulse of the animal system" 411 (emphasis mine). Had Darwin been privy to modern understandings of the chemical networks, computational, and regulatory dynamics involved in genetics, epigenetic inheritance, 42,186 social genomics, 193 and neuroplasticity, 412 it seems likely he would have noted the importance of here-and-now environmental interactions and behavioral responses, and perhaps more pointedly given emotion its functional due. Still, despite his laudable parsimony, Darwin concluded that "the 'language of emotion' is certainly of importance for the welfare of mankind."…”
Section: Resultsmentioning
confidence: 99%
“…Upon the mapping of the genome, however, the subsequent revelations about epigenetic control processes have forever altered the central dogma by elucidating the crucial role of environmental cues, intrinsic signals, and cellular memory in evolution. [186][187][188] Revelations of how supposedly "junk DNA" and noncoding RNA are actually providing ongoing regulatory switching 189,190 ; with relational ifthen rules of engagement that ensure specific gene products are brought into action when and only when appropriate, 191 and mediating the very developmental morphology of an organism 192 as well as its behavior. Revelations of how epigenetic switching yields critical modifications during cellular stress responses, 100,[193][194][195][196] plays a key role in immune functioning, 197 and serves as modulators of neuronal responses, 198 of neural development and neuroplasticity.…”
Section: Purpose In Evolution?mentioning
confidence: 99%
“…The phenotype, on the other hand, is therefore not modified directly, but indirectly through the modification of the genome from which it arises (We simplify here by disregarding e.g. epigenetic inheritance [46]). The accessibility relation at phenotypic level therefore has to be understood as a consequence of the interplay of genotypic accessibility and the GP-map.…”
Section: Phenotype Spacementioning
confidence: 99%
“…A good example is the presence or absence of wings in genetically identical ants according to caste, which simply reflects differential environmental cues (polyphenism: Abouheif & Wray, 2002). Thus, evo-devo studies need to consider not only functional linkages with other genes but also epigenetic constraints on expression (see papers in Jablonka & Lamb, 1995) and environmental cues, potentially spawning yet another discipline that has playfully been titled 'eco-devo'.…”
Section: Understanding Relationshipsmentioning
confidence: 99%